Fluctuations about the Fubini-Lipatov instanton for false vacuum decay in classically scale invariant models - Garbrecht, Björn; Millington, Peter (American Physical Society, 2018)
For a scalar theory whose classical scale invariance is broken by quantum effects, we compute self-consistent bounce solutions and Green's functions. Deriving analytic expressions, we find that the latter are similar to the Green's functions in the archetypal thin-wall model for tunneling between quasi-degenerate vacua. The eigenmodes and eigenspectra are, however, very different. Large infrared effects from the modes of low angular momentum j = 0 and j = 1, which include the approximate dilatational modes for j = 0, are dealt with by a resummation of one loop effects. For a parametric example, this resummation is carried out numerically.